Impact of government subsidies on innovation of Chinese biopharmaceutical firms: Based on kink threshold model - Li, Qing; Di, Jie; Liu, Qingqing (Frontiers in Public Health, 2023)
Based on kink threshold model using data from Chinese biopharmaceutical listed companies from 2013-2019, this study analyzes the impact of government subsidies on innovation inputs and outputs. Government subsidies can stimulate innovation inputs and outputs of biopharmaceutical firms. Meanwhile, such subsidies have a significant threshold effect on innovation inputs and outputs, and there is an optimal interval effect. Additionally, concerning enterprise ownership, government subsidies have a more significant role in promoting innovation of non-state biopharmaceutical firms. Regarding regional differences, such subsidies have a more significant role in promoting innovation of firms in the less economically developed central and western regions. This study reveals the influence pattern of government subsidies, and provides insights and suggestions to formulate subsidy policies and enhance innovation.